2015
DOI: 10.1002/brb3.399
|View full text |Cite
|
Sign up to set email alerts
|

Use of T1‐weighted/T2‐weighted magnetic resonance ratio images to elucidate changes in the schizophrenic brain

Abstract: IntroductionOne leading hypothesis suggests that schizophrenia (SZ) is a neurodevelopmental disorder caused by genetic defects in association with environmental risk factors that affect synapse and myelin formation. Recent magnetic resonance imaging (MRI) studies of SZ brain showed both gray matter (GM) reduction and white matter (WM) fractional anisotropy reduction. In this study, we used T1‐weighted (T1w)/T2‐weighted (T2w) MRI ratio images, which increase myelin‐related signal contrast and reduce receiver‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 78 publications
(181 reference statements)
1
40
1
Order By: Relevance
“…Disorders with a strong demyelinating component such as MS, have consistently showed lower T1‐w/T2‐w values in pathologically vulnerable regions (Beer et al, ; Nakamura et al, ; Righart et al, ). Additionally, lowered T1‐w/T2‐w ratios in several brain regions in schizophrenia (Ganzetti et al, ; Iwatani et al, ) and bipolar disorder patients (Ishida et al, ) have been identified. Recent transcriptomic studies have further observed correlations of the T1‐w/T2‐w intensity in the cortex with expression of genes associated with cortical microcircuit specialization and myelin (Burt et al, ; Ritchie, Pantazatos, & French, ).…”
Section: Discussionmentioning
confidence: 99%
“…Disorders with a strong demyelinating component such as MS, have consistently showed lower T1‐w/T2‐w values in pathologically vulnerable regions (Beer et al, ; Nakamura et al, ; Righart et al, ). Additionally, lowered T1‐w/T2‐w ratios in several brain regions in schizophrenia (Ganzetti et al, ; Iwatani et al, ) and bipolar disorder patients (Ishida et al, ) have been identified. Recent transcriptomic studies have further observed correlations of the T1‐w/T2‐w intensity in the cortex with expression of genes associated with cortical microcircuit specialization and myelin (Burt et al, ; Ritchie, Pantazatos, & French, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hippocampal morphology, we evaluated the T1w/FLAIR signal intensity ratio to probe differences in extra‐hippocampal white matter microstructure. A similar contrast (T1w/T2w) has been recently used to map the myelin content of the cerebral cortex (Glasser and Van Essen, ), and study the effects of ageing (Grydeland, Walhovd, Tamnes, Westlye, & Fjell, ) and disease (Ganzetti, Wenderoth, & Mantini, ; Iwatani et al, ). T1‐weighted and FLAIR images include spatial biases that vary between subjects due to imperfections in the image acquisition techniques, which confound the analysis of T1‐weighted and FLAIR signal intensities.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, methods such as T 1 w/ T 2 w ratio mapping, derived by dividing T 1 w by T 2 w images after basic preprocessing and signal calibration, are technically straightforward, generally have adequate SNR and are highly stable/reliable . Nonetheless, despite the apparent sensitivity to WM microstructural changes, initial claims that this method could be used to assess myelin content have been challenged in more recent studies, suggesting that the T 1 w/ T 2 w ratio more likely represents a general measure of WM microstructure, including myelination, inflammation and other factors …”
Section: Introductionmentioning
confidence: 99%